Levantamento da malacofauna límnica e helmintofauna associada aos moluscos dulcícolas do município de Nossa Senhora de Lourdes, Sergipe - Melo, Ítalo Fernando Lisboa de (2018)
The phylum Mollusca is the second largest group of invertebrates, living in the most varied ecosystems, although it is among the most endangered animals, one of the factors is the introduction of exotic and invasive species in sweet environments. Since prehistory, they are used in food for man, some examples are of medical and veterinary interest, considered hosts of trematódeos. This work aimed to survey the limnic and helmintofauna malacofauna associated with freshwater molluscs of the municipality of. A cross-sectional epidemiological study was carried out from March / 2016 to November / 2017 according to the seasonal differences (dry, rainy and post-rainy periods), based on the collection of molluscs by the water collections of the study area, which were georeferenced using a Global Position System (GPS) receiver. The water collections were analyzed according to the following factors: presence of molluscs; its identification, which occurred through anatomical dissections in stereoscope microscope, conquiliological method and consultations to the specialized references; besides the occurrence of parasitism by the trematodes in limnic molluscs by the techniques of photostimulation and exposure in the dark. The collected material was sent to the Laboratory of Entomology and Tropical Parasitology - LEPaT-UFS, São Cristóvão, SE, where they were kept and investigated for helmintofauna, in addition to these purposes, in the Laboratory of Malacology of the Oswaldo Cruz Institute (LABMAL-IOC) FIOCRUZ, Rio de Janeiro, RJ, the molluscs were fixed and identified. From the water collections found, 34 were georeferenced, 18 (53%) presented molluscs, which were collected according to the periods: dry with 295 (6%), rainy with 3333 (64%) and post-rainy with 1568 (30%), totaling 5196 copies. Of these, 4747 (91%) were gastropods and 449 (9%) bivalves, distributed in 6 families, 1 subfamily and 11 species: Asolene meta and Pomacea lineata (Ampullariidae); Corbicula fluminea and Corbicula largillierti (Corbiculidae); Limnoperna fortunei (Mytilidae); Physa acuta (Physidae); Ancylidae, Biomphalaria straminea, Drepanotrema lucidum, Drepanotrema depressissimum and Drepanotrema cimex (Planorbidae); and Melanoides tuberculata (Thiariidae). Of the 1473 molluscs analyzed for the trematodes, 5 (0.33%) gastropods were infected: one B. straminea specimen presented Vivax; and four M. tuberculata (two emerged Pleurolophocercous and two released Virgulate). The spatial distribution of the molluscs was evidenced in two agglomerates that gathered several types of water collections in the studied area, being that only in the São Francisco river were all the species found. This study is a pioneer for the research area, in addition to notifying mollusks of medical and veterinary importance, positive for several types of cercarians, tends to subsidize the planning of actions of monitoring, prevention and control of helmintoses in order to improve the quality of life of the population. In addition, it contributes to the knowledge of the biodiversity and spatial distribution of the limnic malacofauna of the state of Sergipe.